PENERAPAN IPTEK PADA INDUSTRI TAHU KHAS BANDUNGAN KABUPATEN SEMARANG - Khumaedi, Muhammad; Sudarman, Sudarman; Bintari, Siti Harnina (Universitas Negeri Semarang, 2015)
Science and technology activities for the people (IbM) was conducted with the aim of resolving the problems faced by tofu small industries in Bandungan, Semarang regency, Central Java. There are two IbM partners, namely Mrs. Biyati and Mrs. Widari. There are two aspects of the problems to be addressed, namely the aspects of production and management. As a team implementing these activities are lectures and students with expertise in accordance with the needs of the field. In the implementation of some of the methods that are used to support, among others, with lectures for the theoretical material and motivation, demonstration to deliver material practice / skills, practice directly by the partners, and mentoring activities. In this activity has generated output production and management aspects. Outputs aspects of production: 1) soy grinding machine with a gasoline motor power source so that the sound is smooth and does not interfere with citizens, 2) equipment using steam boiler (steam boiler) so that the kitchen space free of smoke, knows not of bitter and feel better, 3 ) Stamping tools screw system making it easy to operate / lighter. Outputs management aspects: 1) bookkeeping financial / business better, and 2) further increased marketing / marketing a wider range.